2017
DOI: 10.1080/1028415x.2017.1411320
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean-style dietary intervention supplemented with fish oil improves diet quality and mental health in people with depression: A randomized controlled trial (HELFIMED)

Abstract: This is one of the first randomized controlled trials to show that healthy dietary changes are achievable and, supplemented with fish oil, can improve mental health in people with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
297
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(358 citation statements)
references
References 56 publications
12
297
2
3
Order By: Relevance
“…Of those randomized to the therapy groups, 71% attended 8 or more of the 21 sessions. A median of 14 of 15 individual sessions were attended (interquartile range [IQR], [6][7][8][9][10][11][12][13][14][15], and a median of 0 of 6 group sessions (IQR, 0-4) were attended, indicating that adherence to individual sessions was highest.…”
Section: Adherence To Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those randomized to the therapy groups, 71% attended 8 or more of the 21 sessions. A median of 14 of 15 individual sessions were attended (interquartile range [IQR], [6][7][8][9][10][11][12][13][14][15], and a median of 0 of 6 group sessions (IQR, 0-4) were attended, indicating that adherence to individual sessions was highest.…”
Section: Adherence To Interventionsmentioning
confidence: 99%
“…4 Food-related behaviors, like unhealthful eating styles, 5 have been cross-sectionally related to increased depressive symptoms. Recent randomized clinical trials (RCTs) found that dietary improvement strategies reduced depressive symptoms in depressed adults relative to control conditions, 6,7 but there remains a clear lack of RCTs testing dietary strategies to prevent depression. 8 Similarly, observational studies have suggested that lower levels of specific nutrients (eg, omega-3 polyunsaturated fatty acids, folic acid, vitamin D, selenium) are related to higher levels of depressive symptoms.…”
mentioning
confidence: 99%
“…There are numerous health benefits associated with n-3 LCPUFA, including cardiovascular disease [4][5][6], inflammatory disease [7,8] and mental health [9][10][11][12]. Harris and von Schacky postulated that the Omega-3 Index (sum of EPA and DHA expressed as a percentage of total erythrocyte fatty acids) could be a biomarker for cardiovascular disease risk and that an omega-3 index of greater than 8% is optimal [13].…”
Section: Introductionmentioning
confidence: 99%
“…Harris and von Schacky postulated that the Omega-3 Index (sum of EPA and DHA expressed as a percentage of total erythrocyte fatty acids) could be a biomarker for cardiovascular disease risk and that an omega-3 index of greater than 8% is optimal [13]. There is evidence that this omega-3 index biomarker may also be useful in terms of mental health [9][10][11]14].…”
Section: Introductionmentioning
confidence: 99%
“…Intervention studies specifically designed to investigate dietary patterns and depression have begun to emerge only in the last few years. In a study of 85 Australian adults, all aged 18-65 years and with selfreported depression, adherence to a MedDiet was associated with a significantly greater reduction in depressive symptoms (P = 0.03) and improved quality of life (P = 0.04) after 3 months of follow-up, in comparison to the control group, who only attended social group sessions (Parletta et al 2017). These effects were found to be maintained at the 6-month follow-up.…”
Section: Mediterranean Diet Intervention Trials and Depressionmentioning
confidence: 98%